A Meta-Analysis of the Relationship Between Corporate Social Responsibility and Consumer Response in the Chinese Context (Journal of Applied Business and Economics, 2024)
Consumers’ attitudes toward corporate social responsibility (CSR) and their response levels can significantly affect a firm’s behaviors. Based on 61 research papers addressing CSR responses to consumers in China, this study conducted a meta-analysis on three variables: CSR type, CSR characteristics, and CSR publicity behavior, which impact the CSR relationship. The following conclusions are drawn: Corporate social responsibility (encompassing private and public moral dimensions) elicits a positive consumer response, with private moral behavior having a greater positive effect compared to public moral behavior. The four dimensions of CSR characteristics (CSR commitment, CSR level, CSR correlation, and CSR timing) all lead to positive consumer responses. Positive consumer responses also arise from CSR publicity behavior, including publicity initiative and publicity intensity. Additionally, product type, sample time, and sample source have significant moderating effects on these relationships.
Keywords: business; economics; CSR type; CSR characteristic; CSR publicity behavior; consumer response; meta-analysis